Skipped spawning in the Patagonian stock of Argentine Hake (Merluccius hubbsi) - Macchi, Gustavo Javier (2016)
We analyzed the macroscopic and histological maturity data of Argentine hake (Merluccius hubbsi) collected off Patagonia in the spawning area of the Patagonian stock of this species between 2005 and 2014 to determine the frequency of skipped spawning. This study revealed that the only evidence of skipped spawning observed for Argentine hake was the resting stage. Analysis of 58,891 adult females of Argentine hake sampled during their reproductive peak indicates that, annually, between 6% and 22% of them had skipped spawning. These females were located mostly in the periphery of the spawning area, in deeper (>90 m) and colder waters (7–8°C). Individuals that had skipped spawning had a more intense feeding activity and a better nutritional condition (K=0.68–0.75) than females collected in the main spawning area according to the Fulton’s condition index. In contrast, postspawning females showed the poorest condition (K=0.62–0.68) because of the energy cost involved with reproduction. Females that had skipped spawning were mostly young individuals with a modal age of 3 years and a modal size of 38 cm TL. These results indicate that a significant proportion of females that had completed their first annual spawning could skip the next spawning event and stay on the periphery of the reproductive area to feed.